Analisis Tingkat Kepuasan Wajib Pajak terhadap Pelayanan di Kantor Samsat Makassar II - Jesica Jesica; Mesi Melisa Lambe; Sita Yubelina Sabandar; Yohanis Tasik Allo (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
Efforts to improve taxpayer satisfaction are indeed targets in many regions. The key to achieving success is success in understanding taxpayer desires and satisfaction, so that SAMSAT is required to provide quality services and can provide added value to services for taxpayers. This research aims to determine taxpayer satisfaction with services at the Makassar II Samsat Office. The methods used in this research are the observation method and questionnaire method. The population studied in this research is vehicle tax payers at the Makassar II Samsat Office, Biringkanaya District, and the sample in this research is part of the population to be studied, totaling 100 tax payers. In this research, the type of data used is quantitative. The data analysis used is the process of organizing and sorting data into patterns, categories and basic units of description so that the themes can be found and working hypotheses can be formulated as suggested by the data. The results of this research show that the taxpayer satisfaction variable with services has a positive and significant effect which must provide an understanding regarding the level of taxpayer satisfaction with the services provided in order to provide a positive image of the Makassar II Samsat Office.